Efektivitas Pembelajaran Jarak Jauh Jenjang Sekolah Menengah Atas pada masa Normal Baru - Hendro Prasetyono; Hardian Mursito; Heri Nurranto; Sabariyah (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of the study was to determine the effectiveness of distance learning at the high school level. The research uses a quantitative approach with descriptive methods. The sampling technique used in this research is non-probability sampling with purposive sampling technique with a total sample of 257 respondents. Based on the average calculation, the level of achievement of the effectiveness of Distance Learning in the RW 02 Kelurahan Jatiranggon in the new normal period is classified in the Good category, including in the Good category. Constraints that are quite often encountered are in terms of transferring knowledge from teachers to students. Where in practice, students feel the material provided is still difficult to understand, especially in subjects that require practicum, students need special guidelines that can help the practicum process become easier to understand even through a distance learning system. Another thing that is of concern is the low enthusiasm for reading experienced by students.